Lignin dispersions, concentrates and products resulting therefrom

CN118302574BActive Publication Date: 2026-10-16LIGNOFLOW TECH AB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280074405.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-18
Filing Date
2022-11-18
Publication Date
2026-10-16
Estimated Expiration
2042-11-18

AI Technical Summary

Benefits of technology

[0010] The product is a colloidal dispersion comprising a first lignin, a second lignin, and an aqueous liquid continuous phase. The colloidal dispersion has a dispersion pH. The first lignin is a lignin that is substantially insoluble in the aqueous continuous phase at the dispersion pH in the absence of the second lignin, and the second lignin is a lignin that is soluble in the aqueous continuous phase at the dispersion pH in the absence of the first lignin. The colloidal dispersion is a system in which colloidal lignin nanoparticles containing both the first and second lignin are dispersed in an aqueous liquid continuous phase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118302574B_ABST
    Figure CN118302574B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a colloidal dispersion comprising lignin. The colloidal dispersion comprises a first lignin, a second lignin, and an aqueous liquid continuous phase. The colloidal dispersion has a dispersion pH. The first lignin is a lignin that is substantially insoluble in the aqueous continuous phase at the dispersion pH in the absence of the second lignin. The second lignin is a lignin that is soluble in the aqueous continuous phase at the dispersion pH in the absence of the first lignin. The colloidal dispersion is a system in which colloidal lignin nanoparticles comprising the first lignin and the second lignin are dispersed in the aqueous liquid continuous phase. The present disclosure also relates to dispersible lignin concentrates obtainable from such dispersions, and lignin-containing products comprising such dispersions and concentrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to colloidal dispersions containing lignin, and dispersible lignin concentrates obtainable from such dispersions. The invention also relates to lignin-containing products comprising such dispersions and concentrates, and the use of such dispersions and concentrates in the manufacture of lignin-containing products. Background Technology

[0002] Lignin is a renewable biopolymer derived from lignocellulose sources such as wood. Lignin can be obtained, for example, as a byproduct of papermaking, and many pulp mills separate and sell lignin on an industrial scale. Therefore, lignin is a promising renewable material with applications already proposed in a wide range of uses.

[0003] Lignin isolated from sulfite pulping is called lignin sulfonate. Due to the presence of many low pKa sulfonate functional groups, such lignin is readily soluble in aqueous media over a relatively wide pH range and at pH values ​​exceeding the pKa. Commercial uses of lignin sulfonate compositions include their role as plasticizers in concrete and as binders in road dust management applications. Although sulfite pulping accounts for only a small fraction (approximately one-tenth) of chemical pulp production, lignin sulfonates constitute the majority of the current commercial lignin market, at least in part due to their readily water-soluble nature.

[0004] The Kraft process (also known as sulfate pulping) is the primary method for chemical pulp production. Several methods exist for separating lignin from waste sulfate pulping (black) liquor, including the LignoBoost and LignoForce processes. Nevertheless, the market for sulfate lignin is currently much smaller than that for lignin sulfonates. This is likely partly due to the relative difficulty in processing and preparing compositions containing sulfate lignin, attributed to its insolubility in neutral aqueous media (except for a few binary mixtures of water and organic solvents). Sulfate lignin is typically soluble only in relatively strongly alkaline aqueous liquids.

[0005] Numerous methods have been proposed to facilitate the treatment of lignin sulfate by increasing its solubility. Such methods may require the use of uncommon or expensive solvent mixtures, as proposed in Sosa et al. (DOI: 10.1021 / acssschemeng.0c06655), which suggests using deep eutectic solvents to dissolve lignin and make it valuable. Other methods include the chemical derivatization of lignin sulfate to provide products that are structurally and property-closer to lignin sulfonates, as described in patent application WO2021003561A1.

[0006] Improved methods are still needed to make lignin easier to handle. Summary of the Invention

[0007] The inventors of this invention have identified numerous drawbacks of existing methods for simplifying lignin processing. Organic solvent-based methods may require the use of expensive solvents. Solvent recovery necessitates solvent removal, which is energy-intensive and therefore expensive. Chemical derivatization of lignin requires additional process steps, reagents, and / or solvents, thus significantly increasing the cost of lignin compositions. Furthermore, the properties of lignin can be significantly altered due to derivatization, not always in the desired manner. Other common methods for dispersing relatively insoluble components, such as pulverizing (grinding) solid particles, ultrasonic treatment, and aerosol treatment, also have associated disadvantages, primarily in terms of time-dependent solid / liquid phase separation and excessively high costs.

[0008] It would be advantageous to implement methods that overcome or at least mitigate some of the aforementioned disadvantages. In particular, it would be desirable to provide lignin products that can utilize the maximum amount of available lignin while being easier to process and formulate.

[0009] To better address one or more of these problems, products having the features defined in the appended independent claims are provided.

[0010] The product is a colloidal dispersion comprising a first lignin, a second lignin, and an aqueous liquid continuous phase. The colloidal dispersion has a dispersion pH. The first lignin is a lignin that is substantially insoluble in the aqueous continuous phase at the dispersion pH in the absence of the second lignin, and the second lignin is a lignin that is soluble in the aqueous continuous phase at the dispersion pH in the absence of the first lignin. The colloidal dispersion is a system in which colloidal lignin nanoparticles containing both the first and second lignin are dispersed in an aqueous liquid continuous phase.

[0011] It has been discovered that colloidal dispersions can be prepared to allow for the acquisition of stable dispersions with high-quality concentrations of lignin. Such dispersions significantly facilitate the handling and transport of lignin, as well as the formulation of lignin-containing products, because they can be formulated at more or less any desired lignin concentration (up to very high concentrations) with a suitable non-alkaline pH and without typically undesirable components such as organic solvents.

[0012] According to another aspect of the invention, the object of the invention is also achieved by a dispersible concentrate according to the appended claims. The dispersible concentrate can be obtained by dehydrating a colloidal dispersion as described herein and as defined in the appended independent claims. The dispersible concentrate is preferably dried to a total dry matter content of less than 95% by weight, for example, to a total dry matter content of less than 90% by weight, for example, to a total dry matter content of less than 80% by weight.

[0013] Such a concentrate also facilitates the transport of lignin because it presents lignin in a highly concentrated form. Simultaneously, the concentrate is readily redispersible in aqueous media, allowing for easy direct formulation from the concentrate whenever desired.

[0014] According to another aspect of the invention, the object of the invention is also achieved by lignin-containing products according to the appended claims. Lignin-containing products comprise colloidal dispersions and / or dispersible concentrates as described herein and as defined in the appended claims.

[0015] Other objects, advantages and novel features of the present invention will become apparent to those skilled in the art from the following detailed description. Attached Figure Description

[0016] To gain a fuller understanding of the invention and its additional objects and advantages, the following detailed description of embodiments should be read in conjunction with the accompanying drawings, in which the same reference numerals denote the same items in different figures, and in the drawings:

[0017] Figure 1a A graph illustrating the optimal ratio of lignin sulfonate (LS) to softwood sulfate lignin (SKL) for stabilizing colloidal lignin nanoparticles (LNP) at higher total lignin concentrations.

[0018] Figure 1b A graph illustrating the optimal ratio of lignin sulfonate (LS) to softwood sulfate lignin (SKL) for stabilizing colloidal lignin nanoparticles (LNP) at lower total lignin concentrations;

[0019] Figure 2 A graph illustrating the size of LNP as a function of SKL concentration in a dispersion with LS (at an LS / SKL ratio of 4);

[0020] Figure 3 A series of images showing the properties of an LS / SKL gel sample with a lignin content of about 15% by weight before drying are provided, wherein image 1 is the gel before drying, image 2 is the gel after drying, and image 3 is a redispersed dispersion of the gel after drying.

[0021] Figure 4 To show Graphs showing the stability and particle size of lignin sulfonate (LS) and organic solvent (OS) lignin dispersions at different LS:OS ratios;

[0022] Figure 5 A graph showing the stability of Sigma-Aldrich lignin sulfonate (LS) and organic solvent (OS) lignin dispersions at different LS:OS ratios; and

[0023] Figure 6 The graph shows the change in dynamic viscosity and thixotropic properties of LS / SKL nanogels over time. Detailed Implementation

[0024] dispersion

[0025] In the context of this disclosure, a colloidal dispersion is a system in which colloidal lignin nanoparticles (LNPs) comprising a first lignin and a second lignin are dispersed in an aqueous liquid continuous phase. Colloidal lignin nanoparticles are defined as lignin particles having a size of about 1 nm to 1 μm in at least one direction. For example, the dispersion of the present invention may comprise particles with a hydrodynamic diameter of less than about 500 nm, such as less than about 300 nm, such as less than about 200 nm. Such a dispersion may also be referred to as a stable dispersion because it does not exhibit significant precipitation after a prolonged storage timescale (>1 week). Colloidal dispersions may also be simply referred to as dispersions herein. The aqueous liquid phase of the colloidal dispersion may be substantially free of dissolved lignin. For example, less than 5% by weight of total lignin may be dissolved in the aqueous liquid phase.

[0026] Depending on the concentration, the properties of a dispersion can range from a free-flowing liquid at low lignin concentrations to a gel-like consistency at higher lignin concentrations. Such gel-like dispersions are called nanogels, and they can exhibit thixotropic (shear-thinning) properties. However, even the most concentrated gel-like dispersions resist irreversible aggregation and can be readily diluted to provide free-flowing dispersions with particle sizes (hydrodynamic diameters) in the nanoscale range and good polydispersity. This is remarkable because, in other words, it is quite certain in the art that lignin dispersions typically tend to aggregate and form solid precipitates / sediments at high concentrations, elevated temperatures, low pH, and / or high salt concentrations. See, for example, Sewring, T, PhD dissertation, 2019, Chalmers University of Technology; Lievonen, M. et al., Green Chem., 2016, 18, 1416-1422; Lintinen et al., Nordic Pulp & Paper Research Journal, Vol. 32, No. 4, 2017.

[0027] Lignin

[0028] Lignin is an amorphous polyphenolic substance produced by the enzymatic polymerization of lignocellulose materials (such as wood), primarily p-coumarol, coniferyl alcohol, and sinapyl alcohol. The lignin used in this invention can be obtained from any lignocellulose source material. These include wood, grass, algae, annual crops, and agricultural waste. Alternatively, one or more of the lignins can be synthetic lignin.

[0029] Suitable woods can include both softwoods and hardwoods. Softwood species can include, but are not limited to, spruce, pine, fir, larch, cedar, and hemlock. Examples of hardwood species suitable for use as starting materials in this invention include, but are not limited to, birch, oak, poplar, beech, eucalyptus, acacia, maple, alder, aspen, rubber tree, and tung oil. Raw materials used for lignin production can include different softwoods, such as mixtures of pine and spruce. Raw materials can also include non-wood raw materials, such as bamboo, beet pulp, wheat straw, soybean hulls, corn stalks, bagasse, and grasses such as switchgrass and elephant grass.

[0030] Lignin is abundant and biodegradable because it can be produced from a variety of renewable resources such as wood, agricultural residues, and annual crops. Renewable resources refer to materials derived from natural resources that can be restored to their previous stock levels through natural growth or replenishment processes within a reasonable timeframe after exploitation.

[0031] The lignin used can be graded by any method known in the art, such as ultrafiltration or precipitation, to provide purer lignin or lignin with reduced dispersibility.

[0032] Lignin can be used in its neutral or derived forms, such as as salts (e.g., alkali metal salts, such as sodium salts).

[0033] Lignin can be separated and provided in powder form for use in the compositions of the present invention. Alternatively, the lignin of the present invention may comprise or consist of waste pulping liquids. For example, a first lignin may comprise or consist of waste liquids from sulfate pulping or caustic soda pulping processes. A second lignin may comprise or consist of waste liquids from sulfite pulping processes. These waste liquids may be treated, partially treated, or untreated prior to use in the present invention, and therefore may contain varying amounts of other byproducts from the pulping industry, such as hemicellulose, resin acids, and tall oils.

[0034] First lignin

[0035] First lignin is lignin that is substantially insoluble in the aqueous continuous phase at the pH of the dispersion in the absence of second lignin. That is, first lignin is lignin that is substantially insoluble in acidic and neutral aqueous media, for example, lignin that is soluble only at pH values ​​greater than about 10. Such lignin can typically be separated as a byproduct of alkaline or neutral pulping processes used in the manufacture of paper or paperboard. Common such pulping methods include, but are not limited to, sulfate pulping (sulfate pulping), the soda process, and organic solvent processes. First lignin can be obtained by the LignoBoost or LignoForce methods, whereby high-quality lignin is obtained by precipitating lignin through at least partial neutralization of sulfate black liquor with carbon dioxide. The LignoBoost method is further described in: Tomani, Per; The Lignoboost Process; Cellulose Chem Technol., 44(1-3), 53-58 (2010).

[0036] First lignin can be separated as a byproduct of cellulosic ethanol production. When fermenting lignocellulosic biomass feedstock to produce ethanol, typically at least 15% to 30% of the biomass remains unconverted after fermentation. This residual biomass primarily consists of lignin and cellulose.

[0037] The first lignin used in this invention is preferably non-derived lignin. Non-derived lignin means lignin that has not undergone any derivatization after separation. However, as a result of the production / separation process, depending on the method used to separate the lignin, the lignin may undergo some degree of derivatization (e.g., introduction of thiol groups during sulfate pulping), hydrolysis, pyrolysis, repolymerization, or oxidation before or during separation. For example, lignin separated by sulfate pulping and caustic soda pulping is considered non-derived if it does not undergo any further derivatization steps after separation.

[0038] The first lignin may be selected from sulfate lignin, soda lignin, organic solvent lignin, and natural lignin; salts of such lignin; and combinations of such lignin and / or their salts.

[0039] Second lignin

[0040] The second lignin is a lignin that is soluble in an aqueous continuous phase at the pH of the dispersion in the absence of the first lignin. Such lignin can typically be derivatized during or after production / separation using functional groups that make the lignin soluble. These functional groups can be anionic groups, such as sulfonate or carboxylate groups, or cationic groups, such as quaternary ammonium groups. For example, lignin sulfonates separated as a byproduct of sulfite pulping form a large number of sulfonate groups in the primary structure of the lignin. Other lignins suitable for use as the second lignin can be obtained by derivatizing insoluble lignin to make it more soluble. For example, the second lignin can comprise derivatized sulfate lignin isolates, alkali lignin isolates, organic solvent lignin isolates, or other lignin isolates to provide a large number of sulfonate, carboxylate, amine, or quaternary ammonium groups in the primary structure of the lignin. Oxidation of lignin can also make it soluble. Suitable methods for derivatizing and / or oxidizing lignin are known in the art.

[0041] The second lignin can be anionic lignin, that is, lignin that is anionic at the dispersion pH. Anionic lignin is preferably selected from lignin sulfonates, sulfonate-derived lignin, carboxylate-derived lignin, lignin-polymer grafts, non-covalent lignin-polymer conjugates, and oxidized lignin; salts of such lignin; and combinations of such lignin and / or such salts.

[0042] The second lignin can be a cationic lignin, i.e., a lignin that is cationic at the dispersion pH. Cationic lignin is preferably selected from cationic primary amines, cationic secondary amines, cationic tertiary amines and cationic quaternary ammonium-derived lignins; salts of such lignins; and combinations of such lignins and / or such salts.

[0043] Aqueous continuous phase

[0044] The dispersion medium that ultimately forms the aqueous continuous phase is called an aqueous medium. An aqueous medium means (by mass) a liquid medium that primarily contains water. An aqueous medium may consist essentially of only water, or it may consist of a mixture of water and one or more other liquids, such as organic solvents. If it consists of a mixture, the other liquids are miscible or at least dispersible in water. The other liquids may be, for example, polar protic or aprotic organic solvents. Polar means a solvent with a dielectric constant ε greater than 15. Suitable polar protic solvents include, but are not limited to, ethylene glycol, ethanol, methanol, n-propanol, and isopropanol. Suitable polar aprotic solvents include, but are not limited to, dimethylformamide (DMF), acetonitrile (MeCN), dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), and propylene carbonate. An aqueous medium may contain more than 60% by volume, more than 80% by volume, more than 90% by volume, or more than 95% by volume of water.

[0045] Other components

[0046] The dispersions of the present invention may contain other components known in the art, including but not limited to salts, hemicellulose, resin acids, tall oil soaps, dyes, pigments, stabilizers, antioxidants, enzymes, curing initiators, flame retardants, surfactants, and corrosion inhibitors. For example, colloidal dispersions tolerate the presence of salts (e.g., 2M sodium sulfate) without observable aggregation.

[0047] Composition

[0048] The upper limit concentration of lignin in a dispersion appears to be limited only by the water solubility of the lignin used, while the lower limit concentration is not clearly limited; however, very dilute dispersions are generally undesirable from an economic perspective. Therefore, the concentration of colloidal dispersions calculated as the combined total weight of the first and second lignin relative to the total weight of the dispersion can be from about 0.1 wt% to about 80 wt%, for example, from about 3 wt% to about 60 wt%, for example, from about 5 wt% to about 50 wt%, for example, from about 10 wt% to about 40 wt%. The hydrodynamic diameter of colloidal lignin particles is observed to decrease with increasing total lignin concentration. This is contrary to the trend observed in the absence of a second lignin (e.g., lignin sulfonate).

[0049] The optimal ratio of second lignin to first lignin in a composition can vary depending on the concentration of the composition. In concentrated dispersions, the optimal mass ratio of second lignin to first lignin can be about 5:1 or greater. However, in dilute dispersions, the optimal concentration may be lower, for example, 4:1 or greater at a concentration of about 2% by weight. Dispersions with acceptable properties can be achieved by making the mass ratio of second lignin to first lignin range from about 1:90 to about 90:1, for example, from about 2:1 to about 20:1, for example, from about 3:1 to about 10:1, for example, from about 4:1 to about 5:1. Note that the current total market availability of lignin sulfonate to sulfate lignin is currently about 5:1 (1 million tons / year of lignin sulfonate production and 200,000 tons / year of sulfate lignin production), although the future market availability of sulfate lignin may increase significantly. Therefore, the range of acceptable ratios of second lignin to first lignin is well consistent with current and future market availability.

[0050] The pH of the dispersion (referred to herein as dispersion pH) is the pH at which lignin is generally substantially insoluble in aqueous solution, i.e., less than 10 g / L at room temperature, such as slightly soluble, very slightly soluble, almost insoluble, or insoluble. For reference, the solubility of sulfate lignin typically increases significantly at pH 10, for example, for a particular softwood sulfate lignin, from about 1.8 g / L at pH less than 9 to about 100 g / L at pH greater than 11 (see Kong, Fangong et al., “Water soluble kraft lignin–acrylic acid copolymer: Synthesis and characterization.” Green Chemistry 17.8(2015):4355-4366). The dispersion pH can be from about pH 1 to about pH 10, for example, from about pH 3 to about pH 8, or from about pH 5 to about pH 7.

[0051] Production

[0052] The dispersion can be produced in any of a variety of ways, each of which essentially involves forming a mixture of a first lignin and a second lignin in an aqueous phase, and adjusting the pH of the mixture, if necessary, to form a colloidal dispersion. The dispersion can be prepared at temperatures ranging from -10°C to 100°C, preferably from 0°C to 50°C, and even more preferably from 10°C to 30°C. It is known in the art that elevated temperatures can affect the stability of sulfate lignin dispersions (Sewring, T. et al., “Acid Precipitation of Kraft Lignin from Aqueous Solutions: The Influence of pH, Temperature, and Xylan”, Journal of Wood Chemistry and Technology, 2019, 39(1), 1-13) and the hydrophobicity of lignin sulfonates (Li, H. et al., “Effect of temperature on polyelectrolyte expansion of lignosulfonate,” BioRes., 2015, 10(1), 575-587). For these reasons, elevated temperatures are not preferred.

[0053] Before mixing the resulting solutions, the first and second lignins can be dissolved separately in their respective aqueous phases. For the first lignin to dissolve, the pH of the aqueous phase needs to be sufficiently high to provide significant solubility; for example, if the first lignin is sulfate lignin or alkali lignin, then pH > 10. The second lignin is typically soluble even at low pH levels. For example, lignin sulfonates typically exhibit good solubility over a wide pH range from acidic to alkaline, especially in acidic pH where water solubility increases with increasing degree of sulfonation; carboxylated lignins exhibit good solubility at pH levels greater than 4. If waste pulping liquid is used as the source of the first and / or second lignins, the lignin may already be dissolved in the aqueous medium, and the step of dissolving the lignin can be omitted.

[0054] After dissolution, the two separate lignin solutions can then be mixed in an appropriate ratio to achieve the desired ratio of the second lignin to the first lignin. If necessary, the pH of the mixture can then optionally be adjusted to the pH at which the dispersion forms. The dispersion forms at a pH at which the first lignin would normally be insoluble and precipitate from the solution (e.g., about 10 or lower for sulfate lignin). pH adjustment can be done by adding an acid, such as dilute sulfuric acid, to the mixture. However, the solution of the second lignin can itself be acidic, and the pH of the mixture can be adjusted simply by adding the second lignin solution to an alkaline solution of the first lignin. Therefore, adjusting the pH by adding a separate acid may not always be necessary.

[0055] Alternatively, both the first and second lignins can be dissolved separately in an aqueous phase with a pH at which the first lignin is soluble, for example, if the first lignin is sulfate lignin, then the pH > 10. These steps can be performed sequentially in any order, or simultaneously by adding the lignins alone or as a mixture to the aqueous phase. If performed sequentially, it may be preferable to dissolve the first lignin first, as the dissolution of the second lignin typically lowers the pH and may render the first lignin insoluble. After forming the mixture of the first and second lignins, a dispersion can be produced by optionally adjusting the pH as described above.

[0056] Concentrate

[0057] In this way, a dispersion with a high concentration of lignin, as described above, can be formed. However, the dispersion can be dehydrated using conventional methods known in the art to provide a concentrate with even higher dry matter content. Suitable dehydration methods include, but are not limited to, evaporation of excess water and membrane separation. Concentrates produced in this manner have been found to be redispersible in aqueous media, provided that excessive dehydration, such as complete dehydration, is avoided. It is not desirable to be bound by theory; it is considered that the dispersed lignin particles may possess a micellar structure, and that this micellar structure may be damaged or destroyed by excessive drying. It is considered that as long as the micellar structure remains intact, the lignin particles will be redispersible. Therefore, a dispersible concentrate can be obtained by dehydrating the colloidal dispersion to a total dry matter content of less than 95% by weight, for example, less than 90% by weight, or for example, less than 80% by weight.

[0058] application

[0059] Colloidal dispersions and dispersible concentrates disclosed herein are beneficial for the use of lignin and the formulation of lignin products. Therefore, colloidal dispersions and dispersible concentrates can be used in any of the many applications for which lignin has been implemented or proposed. Such applications include, but are not limited to, uses in: paints and coatings, polymer composites, concrete plasticizers, agriculture (fertilizers and pesticide formulations), food and feed (dispersants, antioxidants, etc.), cosmetics (sunscreens; emulsifiers), water treatment (coagulants and adsorbents), and energy storage (porous carbon for electrodes).

[0060] Colloidal dispersions and dispersible concentrates can be used directly to formulate products for such applications, or formulations for such applications may contain materials derived from colloidal dispersions and dispersible concentrates as described herein. For example, colloidal dispersions and dispersible concentrates may be partially or completely dehydrated (e.g., total dry matter content greater than 95% by weight, such as 97%, 99%, or 100%) before use. Alternatively or additionally, the lignin in colloidal dispersions and dispersible concentrates may be reacted through curing, copolymerization, or other derivatization to form new lignin-derived materials.

[0061] Colloidal dispersions and dispersible concentrates can also be used in alternative methods for recovering waste pulping liquids or making waste pulping liquids valuable. For example, the method described herein for producing colloidal dispersions can potentially replace existing LignoBoost and / or LignoForce methods because some technical stages (e.g., lignin oxidation, solid-liquid separation, and washing) can be omitted or implemented in an alternative manner to obtain value-added lignin products.

[0062] The colloidal lignin suspension containing 2M sodium sulfate did not inhibit fungal growth at 38°C, indicating that it is non-toxic to microorganisms.

[0063] Example

[0064] The invention will now be described in more detail with reference to certain exemplary embodiments and the accompanying drawings. However, the invention is not limited to the exemplary embodiments discussed herein and / or shown in the drawings, but may vary within the scope of the appended claims. Furthermore, the drawings should not be considered to be drawn to scale, as some features may have been enlarged for clarity.

[0065] The particle size was determined using a Zeta Sizer instrument (Malvern, UK) via dynamic light scattering (DLS). Measurements were taken of the water-diluted dispersion at 25°C without altering the pH of the dispersion.

[0066] The dynamic viscosity of the lignin nanoparticle dispersion was measured using a rotational viscometer (Viscotech Myr VR 3000) with spindles from R2 to R5 according to the method in ASTM D2196-10. Variations in shear rate were used for extrapolation of the zero-shear viscosity and for determination of the dynamic viscosity as a function of total lignin concentration and pH.

[0067] Example 1

[0068] In the experiment of Example 1, cork sulfate lignin (BioPiva100) from UPM Biochemicals was used as the first lignin, and [the text abruptly ends here, likely due to an incomplete sentence or missing information]. Fabriker's proprietary sodium lignin sulfonate (DS10) serves as a second lignin.

[0069] Dispersions of lignin sulfonate (LS) and cork sulfate lignin (SKL) are produced by dissolving a relevant amount of lignin in a dilute alkali (1M NaOH) and then adjusting the pH of the resulting mixture (using 1M sulfuric acid) to provide a colloidal dispersion somewhere in the range of 2 to 8.

[0070] After preliminary experiments demonstrated the overall feasibility of the method, we tested the concentration range and LS / SKL ratio that achieved stable dispersions. In this context, dispersions with colloidal lignin particle (LNP) hydrodynamic diameters of 480 nm or smaller are considered stable colloidal dispersions. Precipitation of mixtures with LNP hydrodynamic diameters >690 nm was observed, and dispersions with hydrodynamic diameters in the middle range did not exhibit immediate precipitation and could remain stable over long periods. Figure 1a As shown, the optimal LS / SKL ratio can be 5 or higher, because at these ratios, all lignin concentrations are stable. However, stable colloidal dispersions can also be obtained at low LS / SKL ratios and high total lignin concentrations. Furthermore, at LS / SKL concentrations below 2% by weight... Figure 1b When ), the optimal LS / SKL ratio can be reduced to 4.

[0071] as follows Figure 2 As shown, dispersions of LNP with hydrodynamic diameters less than 200 nm can be obtained over a wide concentration range. The dispersions can simultaneously contain up to 10% by weight of SKL and up to 40% by weight of LS (100 mg / ml and 400 mg / ml, respectively).

[0072] At a total lignin concentration of more than 10% by weight, the system forms a gel-like dispersion that can be redispersed or diluted with water. Figure 3The properties of a dispersion containing approximately 15% lignin by weight at an LS / SKL ratio of approximately 5 are shown, along with the effects of drying and redispersion. In the first image, the dispersion exhibits a viscous, gel-like structure. As seen in the second image, drying the sample yields brittle, flaky solids. As shown in the third image, the dried solids can be redispersed in water to provide a homogeneous, free-flowing dispersion.

[0073] Example 2

[0074] In the experiment of Example 2, organic solvent lignin from beech wood pulped with ethanol-water was used as the first lignin. Further details about this lignin can be found in Ago, M. et al., ACS Appl. Mater. Interfaces 2016, 8, 35, 23302–23310. As the second lignin, organic solvent lignin from beech wood pulped with ethanol-water was used. Fabriker’s proprietary sodium lignosulfonate (as in Example 1) or Merck’s proprietary sodium lignosulfonate (LS Sigma, Sigma-Aldrich, SKU 471038).

[0075] Dispersions of lignin sulfonate (LS) and organic solvent lignin (OS lignin) are produced by dissolving a relevant amount of lignin in a dilute alkali (1M NaOH) and then adjusting the pH of the resulting mixture (using 1M sulfuric acid) to provide a colloidal dispersion with a final pH somewhere in the range of 2 to 8.

[0076] Table 1 and Figure 4 The use of organic solvents, lignin, and [other components] was shown. The results were obtained from a mixture of lignin sulfonates.

[0077] Table 1

[0078]

[0079] It can be seen that when mixed with OS lignin, The LS exhibits similar behavior to the LS / KL mixture described in Example 1, and a stable dispersion is obtained at an LS / OS ratio of about 2.5 or greater.

[0080] Discover The dispersion of lignin sulfonate and organic solvent lignin (19% by weight dispersion, LS:OS weight ratio 2:1) can be dried and redispersed in a manner similar to that of the LS / KL dispersion of Example 1.

[0081] Table 2 and Figure 5The results obtained using the organic solvent lignin and a mixture of lignin sulfonate from Sigma-Aldrich (Merck) are shown.

[0082] Table 2

[0083]

[0084] Dispersions produced using lignin sulfonate from Sigma-Aldrich and those produced using lignin sulfonate from [other sources] The dispersions produced from lignin sulfonates exhibited similar characteristics and were stable at LS / OS ratios of approximately 3.75 or greater. However, it was noted that samples of lignin sulfonates from Sigma appeared to contain numerous impurities. For example, the particle size varied significantly if the lignin sulfonates were filtered before the experiment. Therefore, for consistency of results, dissolved lignin sulfonates were filtered through a 0.2-micron filter before dispersion formation.

[0085] Example 3

[0086] The number-weighted particle diameter and zero-shear viscosity of a series of nanogels produced by the method described in Example 1 were measured. Each nanogel had a total lignin concentration of 30% by weight and an LS:SKL ratio of 5:1, but the pH varied from 4.3 to 9.9. The results are shown in Table 3 below.

[0087] Table 3

[0088]

[0089] Each of these nanogels has a gelation time of less than 1 hour. It can be seen that the (zero-shear) viscosity of the gel increases with decreasing alkalinity.

[0090] The dynamic viscosity properties of the nanogel with pH 5.9 prepared above were investigated using ASTM D2196-10 method. The nanogel was stirred at a spindle speed of 6 rpm for 30 minutes, and the viscosity was determined at regular intervals. The results are shown below. Figure 6 middle.

[0091] It can be seen that the nanogel exhibits considerable shear thinning, with the viscosity decreasing from an initial value of over 52,000 mPa·s to less than 38,000 mPa·s after 30 minutes at a constant shear rate of 6 rpm.

[0092] The gel prepared above at pH 4.3 was subjected to dialysis. The gel was transferred to a dialysis bag (Spectra / Por, Sigma Aldrich) with a MWCO of 12kDA to 14kDA and dialyzed against deionized water until the pH reached 6. The gel remained colloidally stable after dialysis, and the dialysis solution remained colorless, indicating that no significant leaching of lignin across the dialysis membrane occurred.

Claims

1. A colloidal dispersion in the form of a thixotropic nanogel, said dispersion comprising a first lignin, a second lignin, and an aqueous liquid continuous phase, The colloidal dispersion has a dispersion pH of 3 to 8. The first lignin is a lignin with a solubility of less than 10 g / L in the aqueous continuous phase at room temperature at the pH of the dispersion in the absence of the second lignin. The second lignin is a lignin that is soluble in the aqueous continuous phase at the pH of the dispersion in the absence of the first lignin.

2. The colloidal dispersion according to claim 1, wherein the pH of the dispersion is between pH 5 and pH 7.

3. The colloidal dispersion according to any one of the preceding claims, wherein the aqueous continuous phase comprises more than 80% by volume of water.

4. The colloidal dispersion according to claim 1 or 2, wherein the aqueous continuous phase comprises more than 90% by volume of water.

5. The colloidal dispersion according to claim 1 or 2, wherein the aqueous continuous phase comprises more than 95% by volume water.

6. The colloidal dispersion according to claim 1 or 2, wherein the mass ratio of the second lignin to the first lignin is 1:90 to 90:

1.

7. The colloidal dispersion according to claim 1 or 2, wherein the mass ratio of the second lignin to the first lignin is 3:1 to 10:

1.

8. The colloidal dispersion according to claim 1 or 2, wherein the mass ratio of the second lignin to the first lignin is 4:1 to 5:

1.

9. The colloidal dispersion according to claim 1 or 2, wherein the colloidal dispersion is calculated as a concentration of 0.1% to 80% by weight of the total combined weight of the first lignin and the second lignin relative to the total weight of the colloidal dispersion.

10. The colloidal dispersion according to claim 1 or 2, wherein the colloidal dispersion is calculated as a concentration of 5% to 50% by weight of the total combined weight of the first lignin and the second lignin relative to the total weight of the colloidal dispersion.

11. The colloidal dispersion according to claim 1 or 2, wherein the colloidal dispersion is calculated as a concentration of 10% to 40% by weight of the total combined weight of the first lignin and the second lignin relative to the total weight of the colloidal dispersion.

12. The colloidal dispersion according to claim 1 or 2, wherein the first lignin is selected from sulfate lignin, alkali lignin, organic solvent lignin, natural lignin, their salts, and combinations thereof.

13. The colloidal dispersion according to claim 1 or 2, wherein the second lignin is anionic lignin.

14. The colloidal dispersion according to claim 1 or 2, wherein the second lignin is selected from lignin sulfonates, sulfonate-derived lignin, carboxylate-derived lignin, oxidized lignin, lignin-polymer grafts, non-covalent lignin-polymer conjugates, their salts, and combinations thereof.

15. The colloidal dispersion according to claim 1 or 2, wherein the second lignin is a cationic lignin.

16. The colloidal dispersion according to claim 1 or 2, wherein the second lignin is selected from lignin derived from cationic primary amines, lignin derived from cationic secondary amines, lignin derived from cationic tertiary amines, or lignin derived from cationic quaternary ammonium, or salts thereof.

17. The colloidal dispersion according to claim 1 or 2, comprising waste pulping liquid from sulfate pulping, caustic soda pulping, organic solvent pulping and / or sulfite pulping.

18. A dispersible concentrate that can be obtained by dehydrating a colloidal dispersion according to any one of claims 1 to 17.

19. A dispersible concentrate that can be obtained by dehydrating a colloidal dispersion according to any one of claims 1 to 17 to a total dry matter content of less than 95% by weight.

20. A dispersible concentrate that can be obtained by dehydrating a colloidal dispersion according to any one of claims 1 to 17 to a total dry matter content of less than 90% by weight.

21. A dispersible concentrate that can be obtained by dehydrating a colloidal dispersion according to any one of claims 1 to 17 to a total dry matter content of less than 80% by weight.

22. A lignin-containing product comprising a colloidal dispersion according to any one of claims 1 to 17 and / or a dispersible concentrate according to any one of claims 18 to 21.

23. Use of the colloidal dispersion according to any one of claims 1 to 17 and / or the dispersible concentrate according to any one of claims 18 to 21 in the manufacture of lignin-containing products.

Citation Information

Patent Citations

  • Process of making sulfonated lignin-based compositions, sulfonated lignin-based compositions so-obtained and their use

    WO2021003561A1